The Moderate Islamic Model in the Thought of Jombang Scholars: Contributions to Policy Harmonization and Interfaith Tolerance - An Najmi, Muhammad Izzul Islam; Ghifari, Reza Iqbal (Tashwirul Afkar, 2023)
This study aims to explore the contributions of prominent Jombang scholars KH. Hasyim Asy‘ari, KH. Wahab Hasbullah, Nurcholish Madjid, and KH. Abdurrahman Wahid in institutionalising the values of moderate Islam within the social policies of the Jombang Regency Government. It also examines the relevance of this local model in constructing global peace through cultural diplomacy and inclusive Islamic values. The research employs a qualitative approach based on library research, using descriptive-analytical analysis and the theoretical framework of neo-institutionalism. The main findings reveal that values such as tasāmuh (tolerance), ta‘ādul (justice), and tawāsuth (moderation) have been systemically internalised through public policies, the pesantren educational system, and interfaith forums. Moderate Islam in Jombang functions not merely as a normative narrative but as a living social praxis with broad impact. This study contributes a novel concept of an institutionalised religious moderation model rooted in local culture, offering potential for replication in other multicultural contexts. The originality of this study lies in its integration of values, actors, and institutional structures into a unified model of locally grounded yet globally resonant moderate Islam. It also provides a new theoretical foundation for understanding the relationship between religion, the state, and civil society in the governance of diversity.